Effect of Diet on Carcass and Meat Quality in Rabbits (Indian Journal of Animal Production and Management, 2024)
A trial was conducted to assess the growth  performance of Soviet Chinchilla rabbit under  different feeding regimes at Livestock Farm  Complex, Madhavaram Milk Colony, Chennai-51.  Thirty Soviet Chinchilla weaned bunnies of both  sexes aged around six weeks were randomly  selected and divided into three groups namely T1  (Guinea grass + Concentrate), T2 (Hydroponic  Maize + Concentrate) and T3 (Hydroponic Cowpea  +Concentrate). All the groups were reared under  similar intensive system of management. The  dressing percentage of rabbits in T1, T2 and T3  were 59.40±0.87,60.20±1.50 and 61.20±0.97  respectively. There was no significant difference in  dressing percentage between the treatment groups.  The meat bone ratio in T3 was significantly higher  than T1 and T2. The carcass characteristics did not  differ between the treatment groups. It is concluded  from this study the hydroponic fodder production  technology can be recommended for broiler rabbit  production in urban, peri-urban areas where land  availability for fodder production is a constraint.
Keywords: rabbits; guinea grass; hydroponic maize; hydroponic cowpea; carcass characteristics